Sharing the Responsibility for Teacher Preparation: Collaborative Design of a Teaching Observation Rubric - Yun, Cathy; Bennett, Lisa (Educational (Re)naissance, 2018)
This case story describes the collaborative development and use of a teaching observation rubric to support and scaffold evidence-based changes in the focal educator preparation program (EPP). The case highlights the power of EPP-district collaborations for improving the teaching and coaching practices for both stakeholders while strengthening trust. Additionally, this case demonstrates how the focal EPP worked with districts to ease preservice-to-inservice transitions for novice teachers, through development of a feedback instrument that spans the transition, thereby decreasing teacher attrition within the first three years on the job.